2024
DOI: 10.3389/fevo.2024.1346795
|View full text |Cite
|
Sign up to set email alerts
|

Advancing bee conservation in the US: gaps and opportunities in data collection and reporting

Josée S. Rousseau,
S. Hollis Woodard,
Sarina Jepsen
et al.

Abstract: IntroductionBee conservation in the US is currently hindered by challenges associated with assessing the status and trends of a diverse group of >3000 species, many of which are rare, endemic to small areas, and/or exhibit high inter-annual variationin population size. Fundamental information about the distribution of most species across space and time, thus, is lacking yet urgently needed to assess population status, guide conservation plans, and prioritize actions among species and geographies.Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Our work shows the feasibility of developing fine-scale maps for guiding conservation of data-limited taxa like bees, despite insufficient historical survey effort, dependence on unstructured collection records, and taxonomic biases (Chesshire et al, 2023;Rousseau et al, 2024). While monitoring programs are taking shape to address these data deficiencies, many large-scale conservation actions are slated to occur by the end of the decade under the 30x30 framework, that strives for 30% of land area to be conserved by 2030 (Dinerstein et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Our work shows the feasibility of developing fine-scale maps for guiding conservation of data-limited taxa like bees, despite insufficient historical survey effort, dependence on unstructured collection records, and taxonomic biases (Chesshire et al, 2023;Rousseau et al, 2024). While monitoring programs are taking shape to address these data deficiencies, many large-scale conservation actions are slated to occur by the end of the decade under the 30x30 framework, that strives for 30% of land area to be conserved by 2030 (Dinerstein et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…And more broadly, iNaturalist data are coming to dominate natural history databases. Across the United States, Rousseau et al (2024) found that 92% of bee records on GBIF between 2019 and 2021 were from iNaturalist. However, these numbers may be biased in part because many records from other sources collected during those years may not be processed and digitized yet.…”
Section: Discussionmentioning
confidence: 99%